The Platelet Response to Tissue Injury - Eisinger, Felix; Patzelt, Johannes; Langer, Harald F. (Frontiers in Medicine, 2018)
In recent years, various studies have increasingly explained platelet functions not only in their central role as a regulator in cellular hemostasis and coagulation. In fact, there is growing evidence that under specific conditions, platelets act as a mediator between the vascular system, hemostasis and the immune system. Therefore, they are essential in many processes involved in tissue remodeling and tissue reorganization after injury or inflammatory responses. These processes include the promotion of inflammatory processes, the contribution to innate and adaptive immune responses during bacterial and viral infections, the modulation of angiogenesis and the regulation of cell apoptosis in steady-state tissue homeostasis or after tissue breakdown. All in all platelets may contribute to the control of tissue homeostasis much more than generally assumed. This review summarizes the current knowledge of platelets as part of the tissue remodeling network and seeks to provide possible translational implications for clinical therapy.